Extended Phase-Space Methods for Enhanced Sampling in Molecular Simulations: A Review - Fujisaki, Hiroshi; Moritsugu, Kei; Matsunaga, Yasuhiro; Morishita, Tetsuya; Maragliano, Luca (Frontiers in Bioengineering and Biotechnology, 2015)
Molecular Dynamics simulations are a powerful approach to study biomolecular conformational changes or protein-ligand, protein-protein and protein-DNA/RNA interactions. Straightforward applications however are often hampered by incomplete sampling, since in a typical simulated trajectory the system will spend most of its time trapped by high energy barriers in restricted regions of the configuration space. Over the years, several techniques have been designed to overcome this problem and enhance space sampling. Here, we review a class of methods that rely on the idea of extending the set of dynamical variables of the system by adding extra ones associated to functions describing the process under study. In particular, we illustrate the Temperature Accelerated Molecular Dynamics (TAMD), Logarithmic Mean Force Dynamics (LogMFD), and Multiscale Enhanced Sampling (MSES) algorithms. We also discuss combinations with techniques for searching reaction paths. We show the advantages presented by this approach and how it allows to quickly sample important regions of the free energy landscape via automatic exploration.